The Effect of Massage on the Development of 3-Month-Old Babies - Finta Isti Kundarti; Siska Woro Andhani; Dwi Estuning Rahayu; Eny Sendra (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Infant development is a crucial Element of a kid’s maturation and progress encompassing motor, language, social, and cognitive skills. Early stimulation, such as infant massage, can stimulate the core neurological framework manages essential physiological processes and accelerate the achievement of age-appropriate developmental milestones. This research intended to evaluate the effect of infant massage on babies' development aged three months. The study employed a semi-experimental approach utilizing a before-and-after evaluation with a comparison group structure. The participants were made up of 70 3-month-old infants, divided into two groups: 35 in the therapy cluster at Balowerti Community Health Center and 35 in the control group at Sukorame Public Wellness Facility. The selection method applied was purposive sampling. The intervention provided to the treatment group consisted of 15 minutes of infant massage twice a week for four weeks, performed by trained mothers. The control group received only standard developmental monitoring care. Developmental data were measured using the Pre-Developmental Screening Questionnaire (KPSP). Analysis used the Mann-Whitney U Test and the Wilcoxon Signed Rank Test. The findings indicated a notable improvement in developmental metrics among the intervention group (mean increased from 5.49 to 7.06; Z = -4.326; p = 0.000), Meanwhile, the control group exhibited no substantial variation (p = 0.343). Regular infant massage is effective in improving the development of 3-month-old infants. Massage can be incorporated into a family-based early stimulation program.